2021
DOI: 10.1029/2021wr029584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poroelastic Coupling and Fracture Dynamics on Solute Transport and Geomechanical Stability

Abstract: In many applications, a key objective of the numerical model built to simulate the processes is to quantify the mixing between the injected and resident fluids and quantify the extent of the associated mixing zone (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Realistic modelling relies not only on accurate data concerning material parameters, but also on appropriate spatial distribution of such parameters (Houben et al, 2018;Irvine et al, 2015;Kalbus et al, 2009). Typically, distributed material parameters are generated by stochastic random fields based on an a priori statistical distribution (Vanmarcke et al, 1986). Although random fields have proven to be useful, they do not capture the usual continuity of material parameters (Strebelle, 2002).…”
Section: Herten Aquifer Data Set Descriptionmentioning
confidence: 99%
“…Realistic modelling relies not only on accurate data concerning material parameters, but also on appropriate spatial distribution of such parameters (Houben et al, 2018;Irvine et al, 2015;Kalbus et al, 2009). Typically, distributed material parameters are generated by stochastic random fields based on an a priori statistical distribution (Vanmarcke et al, 1986). Although random fields have proven to be useful, they do not capture the usual continuity of material parameters (Strebelle, 2002).…”
Section: Herten Aquifer Data Set Descriptionmentioning
confidence: 99%
“…In the case of injected solute–ambient fluid systems, this is equivalent to the mixture viscosity's dependence on the injected solute concentration. As a result, the solute plume's mobility and, consequently, mixing are significantly affected by the viscosity contrast (Jha, Cueto-Felgueroso & Juanes 2011 a ; Nijjer, Hewitt & Neufeld 2018; Tran & Jha 2020, 2021; Bonazzi et al. 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have concluded that in‐fracture aperture variability, whether natural or caused by external stress, can have significant effects on fluid flow and transport in a single fracture (Cardenas et al., 2007; Dang et al., 2019; de Dreuzy et al., 2012; Frampton et al., 2019; Hanna & Rajaram, 1998; Hyman et al., 2021; Kang et al., 2016; Makedonska et al., 2016; Pandey et al., 2015; M. Wang et al., 2016; Zhou et al., 2018). Within the context of network flow, there is substantially less research than at the single fracture scale (Garipov et al., 2016; Hyman et al., 2016, 2019b, 2020; Kang et al., 2019, 2020; Lei et al., 2017; Maillot et al., 2016; McClure et al., 2016; Sweeney & Hyman, 2020; Tran & Jha, 2021). Nonetheless, a common finding amongst these studies is that when the aperture distribution widens, for example, due to different fractures opening and closing from stress, flow channelization increases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has studied the link between fracture-to-fracture aperture heterogeneity from different perspectives than what we have done here and could be re-interpreted in light of our results. For one aspect, it has been published that under anisotropic mechanical stress fields, aperture distributions may widen and become more variable(Garipov et al, 2016;Kang et al, 2019;Lei et al, 2017;McClure et al, 2016;Sweeney & Hyman, 2020;Tran & Jha, 2021). If the network is short circuited relative its original topology via connected shear fractures, one can expect early arrival times of solutes relative to the original network.…”
mentioning
confidence: 99%
See 1 more Smart Citation